Personalizing survival predictions in advanced colorectal cancer: The ARCAD nomogram project - Sjoquist, KM; Renfro, LA; Simes, RJ; Tebbutt, NC; Clarke, S; Seymour, MT; Adams, R; Maughan, TS; Saltz, L; Goldberg, RM; Schmoll, H-J; Van Cutsem, E; et al. (Oxford University Press, 2017)
Background Estimating prognosis on the basis of clinicopathologic factors can inform clinical practice and improve risk stratification for clinical trials. We constructed prognostic nomograms for one-year overall survival and six-month progression-free survival in metastatic colorectal carcinoma by using the ARCAD database.